(untitled) (Revista de História da UEG (REVHIST), 2022)
This paper brings an analysis about how the inquisitors received the testimonies of boys who had denounced in the Inquisitorial Tribunal different sexual practices, including sodomy, perpetrated by two priests in the first half of the 17th century. In 1638, João Botelho, who was a professed friar of the Hieronymites for about 20 years – until he was expelled –, a singing master, and had achieved the degree of procurator of the Monastery of Mato; and Francisco Dias Palma, priest of the Order of Santiago, were imprisoned, respectively, by the Holy Office of Lisbon and Évora. Botelho’s lawsuit began with the boys’ denunciations, who accused him of sodomitical practices, and Dias Palma’s one began with the testimonies of adult men, who accused him of trying to sodomize a 12-year-old boy, who was called to the Holy Office to confess the priest’ sexual practices. At a time when childhood and innocence meanings were very different from nowadays’ comprehensions, and when social hierarchies were well demarcated, what was the inquisitorial look at the accusations of minors in both processes? Considering that the social status of the boys’ families was heterogeneous, we sought to scrutinize whether the minors and their testimonies were equally evaluated by the inquisitorial judges. Keywords: Portugal. Inquisition. Sodomy. Boys. Priests.